Caregiver Sexual and HPV Communication Among Female Survivors of Childhood Cancer. (May 2016) - Peasant, Courtney; Foster, Rebecca H.; Russell, Kathryn M.; Favaro, Brianne E.; Klosky, James L.
Human papillomavirus (HPV) vaccination is recommended for all female survivors of childhood cancer; yet, it is underused. Parent-child sexual communication and health care provider recommendation for HPV vaccination influence familial vaccination decisions. However, caregivers may be less likely to discuss sexual health issues with survivors as compared to healthy peers. Therefore, this study compared mothers of daughters with/without history of childhood cancer on measures of sexual communication, HPV-specific communication, and health care provider recommendation for HPV vaccination, and examined the effects of sociodemographic and medical factors on these measures. There were no differences between mothers of survivors/noncancer survivors on the outcomes ( P s > .05). Among all mothers, daughter's age was associated with sexual communication ( P s < .05). Household income and daughter's age were associated with health care provider recommendation for vaccination ( P s < .05). Among mothers of survivors, daughter's age at diagnosis was associated with sexual communication, HPV-specific communication, and health care provider recommendation for vaccination ( P s < .05). Findings have implications for the role of health care providers as advocates for mother-daughter sexual communication and HPV vaccination, especially among survivors of childhood cancer.